2021
DOI: 10.1097/md.0000000000026912
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic patterns in outpatients with schizophrenia in China

Abstract: It is essential to monitor pharmacological treatment for schizophrenic outpatients regularly in clinical practice. Especially in China, the situation of common prescribing patterns remains unclear. The objective of this study is to reveal real-world treatment prescription patterns of antipsychotics for schizophrenia patients in a representative large tertiary hospital in China. This study is a cross-sectional observational analysis of outpatients with schizophrenia in a large tertiary psychiatric ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…APs are generally regarded as the first-line treatment for patients with schizophrenia and were given to the majority of these patients, although a sizable number of studies reported patients who received no dispensed APs. The frequency of AP use was 67-98.8% in schizophrenia patients in these studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Most patients (52.3% to 90.9%) were on AP monotherapy [28][29][30][31]34,38,[40][41][42][43][44][45][46][47][48][49][50][51][52], except for five studies [27,[53][54][55][56].…”
Section: Antipsychotic Prescription Trends and Clinical Correlatesmentioning
confidence: 76%
See 1 more Smart Citation
“…APs are generally regarded as the first-line treatment for patients with schizophrenia and were given to the majority of these patients, although a sizable number of studies reported patients who received no dispensed APs. The frequency of AP use was 67-98.8% in schizophrenia patients in these studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Most patients (52.3% to 90.9%) were on AP monotherapy [28][29][30][31]34,38,[40][41][42][43][44][45][46][47][48][49][50][51][52], except for five studies [27,[53][54][55][56].…”
Section: Antipsychotic Prescription Trends and Clinical Correlatesmentioning
confidence: 76%
“…The frequency of AP use was 67-98.8% in schizophrenia patients in these studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Most patients (52.3% to 90.9%) were on AP monotherapy [28][29][30][31]34,38,[40][41][42][43][44][45][46][47][48][49][50][51][52], except for five studies [27,[53][54][55][56]. Monotherapy AP prescription generally showed an upward trend over the years [38], particularly for second-generation AP (SGA) monotherapy [43].…”
Section: Antipsychotic Prescription Trends and Clinical Correlatesmentioning
confidence: 76%
“…Recent epidemiological studies have found that the prescription rates of LAI in clinical settings vary between 20 and 40% in European countries ( 23 , 24 , 36 ), but only 10.7% of respondents have ever used LAI in this study. A study of outpatients has also shown that only about 5% of patients used LAI in China ( 37 ), which is lower than that in developed countries. Mace et al's investigation has shown that 48% of the community patients in Britain were treated with LAI ( 38 ), while Sugawara et al has reported that 18.2% of outpatients in Japan use LAI ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first-generation antipsychotics (FGAs) were introduced in the 1950s and 1960s, followed by second-generation antipsychotics (SGAs) in the 1990s. While both FGAs and SGAs are effective in reducing positive symptoms of schizophrenia, SGAs have fewer side effects and are better tolerated by patients (21). Recently, several new antipsychotic medications, such as lumateperone and cariprazine, have been approved for the treatment of schizophrenia (22).…”
Section: Introductionmentioning
confidence: 99%